Where on the Differential Is Eisenmenger Syndrome in a Patient Without Prior Cardiopulmonary Disease? - Kellish, Alec S (Cureus, 2020)
Pulmonary hypertension (PH) can occur in patients with undiagnosed congenital heart disease, like atrial septal defects (ASDs), causing chronic left-to-right shunting. This may ultimately result in Eisenmenger physiology or syndrome (ES), a reversal of left-to-right shunting, resulting in a right-to-left shunt, thereby causing deoxygenated blood to enter systemic circulation as it bypasses the lungs. Development of PH due to an ASD is uncommon, and the occurrence of ES is <1% as most ASDs are corrected early in life. We present a 28-year-old female presenting with new-onset dyspnea found to have an undiagnosed ASD with ES. A 28-year-old female without past medical history presented to the emergency department after a chest x-ray performed by her primary care physician (PCP) showed dilation of the pulmonary artery concerning PH. The patient reported a three-month history of progressively worsening intermittent palpitations and dyspnea, now unable to walk more than one block without becoming dyspneic. Further imaging studies revealed a 1.4 centimeters (cm) secundum ASD, 4.4 cm dilatation of the PA, a mean pulmonary artery pressure (PAPm) of 132 millimeters (mm) mercury (Hg), and Eisenmenger physiology. She was placed on pulmonary vasodilators and iron supplementation to address an underlying iron-deficiency anemia. The patient is stable on her current regimen and is undergoing evaluation for possible heart-lung transplantation at an outside hospital. Dyspnea is one of the top 10 most common indications for emergency room visits annually. The differential diagnosis for dyspnea is vast, with ES, affecting only 0.8 in 1 million, far down on the list of possibilities, thus requiring high clinical suspicion to prompt further evaluation. Ultimately, the condition is preventable with early identification of underlying structural abnormalities for which definitive treatment options exist and are readily available, dramatically improving the prognosis if implemented before ES develops.